West Java Potato Farmers’ Preference on The Quality Characteristics of Indonesian Vegetables Research Institute Potato Varieties - Asma Sembiring; K. Kusmana (Jurnal Ilmiah Teknik Industri, 2020)
The availability of a high-quality potato seed will affect the increasing of Indonesia potato production. Indonesia Vegetables Research Institute (IVegRI) attempts to produce various high-quality potato varieties. The potatoes are needed to be disseminated to users. Therefore, they could create benefits in terms of increasing farmers' production and revenue. The objective of the study was to identify West Java potato farmers' preference for the seven potato varieties that have been released by IVegRI. The survey was carried out in Garut district, West Java province, Indonesia. Total, 32 potato farmers, participated in the survey from January to September 2019. The Perceived Quality (PQ) was used to analyze data. The result indicates three potato varieties preferred by potato farmers were Dayang sumbi, Sangkuriang, and Medians, respectively. The result would be useful for the IVegRI to create better potato varieties in the future.